2017
DOI: 10.4025/actascianimsci.v39i1.33070
|View full text |Cite
|
Sign up to set email alerts
|

<b>Effect of using the Matrix Values for NSP-degrading enzymes on performance, water intake, litter moisture and jejunal digesta viscosity of broilers fed barley-based diet

Abstract: ABSTRACT. In this study, we have evaluated the effect of three multi-enzymes nutrient matrix values and compared the results with that fed barley and the corn diets without enzyme. In entire period, addition of all enzymes to the barley-based diet significantly (p < 0.05) increased feed intake (FI) and the highest intake was for birds that fed enzyme A (p < 0.05). Overall, from 0 to 42 days, average daily gain (ADG) was significantly (p < 0.05) increased by enzyme and birds fed enzyme A had the highest body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
1
9
1
1
Order By: Relevance
“…This increase is usually in the range of 50–150 kcal/kg feed depending on the nature and quality of the ingredients used in the diet and the nature of the used enzyme [ 29 ]. NSP-degrading enzymes can reduce the increase in the viscosity of digesta resulting from sugars leaking from the grain cell walls by releasing the nutrients trapped in the feed cellular matrix [ 30 ] because the viscosity is larger in smaller birds and decreases with age.…”
Section: Introductionmentioning
confidence: 99%
“…This increase is usually in the range of 50–150 kcal/kg feed depending on the nature and quality of the ingredients used in the diet and the nature of the used enzyme [ 29 ]. NSP-degrading enzymes can reduce the increase in the viscosity of digesta resulting from sugars leaking from the grain cell walls by releasing the nutrients trapped in the feed cellular matrix [ 30 ] because the viscosity is larger in smaller birds and decreases with age.…”
Section: Introductionmentioning
confidence: 99%
“…However, Attia et al (2014) found that the addition of multiple enzymes increased the percentage of carcass weight and total edible parts of broiler chickens. The increase in the percentage of carcass weight was due to a decrease in the inedible parts of broiler chickens and the weight of the small intestine (Moftakharzadeh et al, 2017).…”
Section: Duck Performancesmentioning
confidence: 97%
“…The results of these studies indicated that the addition of both individual enzymes or multiple enzymes in feed-based rations containing a high quantity of non-starch polysaccharides had a positive effect on the duck performance, as was reported by some researchers on broiler chickens (Akyurek et al, 2009;Gitoee et al, 2014;Goli & Shahryar, 2015;Moss et al, 2017;Teymouri et al, 2018;Effiong et al, 2019). The improvement in performance was thought to be due to an increase in the digestibility of food substances, including crude protein, crude fiber, and ash (minerals) (Kang et al, 2013;Zeng et al, 2015;Moss et al, 2017;Effiong et al, 2019) and a decrease in the viscosity of gastrointestinal digesta (Moftakharzadeh et al, 2017;Teymouri et al, 2018).…”
Section: Duck Performancesmentioning
confidence: 99%
“…Interestingly, in their study addition of phytase as only enzyme increased heat loss of broilers. While viscous grains such as wheat or barley increase the relative size and length of gastrointestinal tract of broiler chickens (Fan, Han, Xu, Wang, & Shi, 2009;Moftakharzadeh et al, 2017), addition of enzyme to NSP containing diets in many studies has reduced relative weight of these energetically active organs (Rodríguez et al, 2012;Wang, Qiao, Lu, & Li, 2005). One possible reason for lower HP in enzyme treatments would be lower maintenance of digestive active organs induced by enzyme supplementation.…”
Section: Heat Productionmentioning
confidence: 99%
“…Anti-nutritional compounds known as non-starch polysaccharides (NSPs) are the most important factor has confined feeding wheat to broiler chickens especially at early days of growing period. The presence of soluble NSP can cause highly viscous conditions in the gastrointestinal tract and decrease contact between digestive enzymes and substrates, resulting in poor nutrient digestion and performance broiler chickens (Choct, Sinlae, Al-Jassim, & Pettersson, 2006;Moftakharzadeh, Moravej, & Shivazad, 2017;Nian, Guo, Ru, Li, & Peron, 2011). Supplementation of wheat-based diet with exogenous glycanase appear to enhance growth performance and energy utilization alongside with (Hashemipour, Khaksar, Rubio, Veldkamp, & Van Krimpen, 2016;Kiarie, Romero, & Ravindran, 2014;Pirgozliev et al, 2015;Wu, Choct, Wu, Liu, & Swick, 2017) or without reduction of intestinal viscosity of broilers (Amerah, Ravindran, Lentle, & Thomas, 2008).…”
Section: Introductionmentioning
confidence: 99%